The waistline of Indian men is expanding faster than women with general obesity and abdominal obesity reaching a epidemic in Indian subject with diabetes - R, Lalitha; B Shetty, Surekha; Kumar R, Anil (International Journal of Medical Research and Review, 2016)
Background & Objectives: People with obesity and overweight are increasing in India. This study aimed at determining the prevalence of generalized and abdominal obesity in diabetics and comparison between genders. Methods: An observational study held at Diabetes centre, between 2013-2014. Classification of obesity was done using WHO and IDF criteria for BMI in Asians, while Waist Circumference and WHR per IDF criteria. WHO Asia Pacific guidelines were used to define overweight [body mass index (BMI) ≥23 kg/m2 but <25 kg/m2, generalized obesity, BMI≥25kg/m2), abdominal obesity, waist circumference ≥90 cm in men, ≥80cm for women). 4504 subjects (men 2741, women 1763) with diabetes aged ≥ of 25 were recruited. Results: The prevalence rates were 2, 13, 31 & 54 % women and 3, 23, 48, & 26% men were lean, normal, overweight and obese respectively. Comparing the waist circumference between men and women with IDF criteria 65% men (n=9235) and 89 %( n=8175) have a WC above the normal. Waist hip ratio, identified higher prevalence rate in men (89%) compared to women (76%) and WHR was a sensitive index compared to WC. Interpretation & Conclusions: Higher prevalence of abdominal obesity compared to general obesity in diabetic population affected both genders similarly. Both general and abdominal obesity prevalence are higher in women than men. Our study found that AO had a higher prevalence in men contrary to the belief that women have higher AO. Abdominal obesity is directly linked to increased morbidity.